Business strategies and tournament incentives: Evidence from China - Li Sun; Ahsan Habib; Hedy Jiaying Huang (BRQ Business Research Quarterly, 2024)
We investigate the association between business strategy and firm-level tournament incentives in China and find that business strategy is associated with tournament incentives positively. We further find that this positive relationship manifests itself in local, but not central, state-owned enterprises (SOEs). In addition, we also offer some evidence that foreign institutional investors play a moderating role on the positive association between business strategy and tournament incentives. Our study fills a gap in the existing tournament literature by incorporating business strategy as an important determinant of tournament incentives in China.
Keywords: 650; Business strategies; China; defender; prospector; tournament incentives; M10; G30; J33